Mortgaged Minds: Faculty-in-Debt and Redlining Higher Education - Scheper, Jeanne (Radical Teacher, 2017)
While undergraduate student loan debt continues to be “hard to register,” there are other conditions and effects of the student loan debt spiral that remain relatively invisible, unexamined, and certainly receive less attention in news headlines or on the op-ed pages about the fiscal cliff of education debt. These are the effects of this debt spiral on graduate education, faculty composition, and knowledge production itself. This article highlights how the debt load of faculty is part of the current student loan debt spiral, yet its effects on the working conditions of faculty, the learning conditions of students, and, importantly, the production of knowledge in the university remain underexamined.